Pengaruh Relaksasi Otot Progresif terhadap Kelelahan dan Kualitas Tidur pada Petani Penyadap Karet di PTPN XII Kebun Kalisanen Jember - Wahyu Adinda Yuli Pratiwi; Emi Wuri Wuryaningsih; Enggal Hadi Kurniyawan (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Farmers often experience fatigue due to excessive workload and working hours. People with excessive fatigue will have sleep difficulty. The purpose of this study was to analyze the effect of progressive muscle relaxation on fatigue and sleep quality on rubber tapping farmers at PTPN XII Kalisanen Garden, Jember Regency. The design used is Quasy Experimental with a pretest and posttest design with control group design. The sampling technique was simple random sampling involving 40 farmers (20 respondents in the intervention group and 20 respondents in the control group). Data collection for fatigue using the Fatigue Severity Scale questionnaire and sleep quality using the Pittsburg Sleep Quality Index questionnaire. The results of the effect of PMR on fatigue in the intervention and control groups using the independent t-test obtained results with of p-value 0,000 <0,05, which means that there was an effect of PMR on fatigue in the intervention and control groups. The results of the influence of PMR on sleep quality in the intervention and control groups using the Mann- Whitney test obtained results with of p-value 0,000 <0.05 which means that there was an effect of PMR on sleep quality in the intervention and control groups. PMR activates the sympathetic and parasympathetic nervous system that works mutually so that it can reduce muscle tension and make it easy to sleep. in conclusion, PMR can be used to reduce fatigue and can improve sleep quality.